2018
DOI: 10.4172/1758-4272.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and leflunomide survival in patients with psoriatic arthritis

Abstract: The objectives of this study were to estimate the survival rate of the most frequently used DMARDs in a cohort of PsA patients and factors associated with a higher survival rate. Methods: Patients ≥ 18 years of age with PsA according to CASPAR criteria, belonging to the RAPSODIA cohort were studied. Socio-demographic, clinical and treatment data were collected. Statistical analysis: Kaplan Meier survival curves and log rank were used to analyse and compare drugs' survival rate. Cox proportional analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Younger individuals had a higher discontinuation rate. This finding is similar to an Argentine cohort, which found that patients older than 50 years treated with leflunomide had a higher persistence to treatment ( Landi et al, 2018 ). This effect was also observed for methotrexate, but the patients treated with this drug were on steroids ( Ribeiro da Silva et al, 2019 ).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Younger individuals had a higher discontinuation rate. This finding is similar to an Argentine cohort, which found that patients older than 50 years treated with leflunomide had a higher persistence to treatment ( Landi et al, 2018 ). This effect was also observed for methotrexate, but the patients treated with this drug were on steroids ( Ribeiro da Silva et al, 2019 ).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, patients who were treated with leflunomide and methotrexate were the most persistent, while individuals taking ciclosporin and sulfasalazine showed a higher rate of discontinuation in the treatment of PsA. Methotrexate and leflunomide are usually the csDMARD investigated in observational studies for PsA, and the results are comparable between them ( Landi et al, 2018 ; Ribeiro da Silva et al, 2019 ). Sulfasalazine appeared only in one study versus methotrexate, with a worse result of persistence ( Jacobs et al, 2020 ).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations